Investigasi Airtanah Melalui Geolistrik di Darmaga, Bogor - Roh Santoso Budi Waspodo (PERTETA, 2002)
Groundwater is an important resource of water supply in the highly populated city. Groundwater availability in aquifer is determaneted by morfological hydrological and geological factors. Geological factors includes shape and distribution of rock, difference and distribution of layer and geological structure. One method to investigate the groundwater potential can be used geolistric method, so can be represent about distribution, locations and depth of rock layers in subsurface at the research area. The conductivity hydrolic values in Darmaga, Bogor range from 0.85 to 2.90 m/day or 0,001 - 0,04 and the value of expect discharge is 10 s/d 20 liters/sec.